CONNOTATIONS AND ASSOCIATIONS OF THE ADJECTIVE «GREY» - M. V. Denisenko (Вестник Кемеровского государственного университета, 2013)
The lexical meaning is a very complex structure. Different researchers distinguish different amounts of elements in its structure. There are also multiple approaches to defining connotation. The notion of connotation is unclear and indistinct. This term has numerous synonyms. The most broadly, connotation means additional information. Connotation is also some kind of figurative meaning in speech, as it reflects the native speaker’s associations and cultural traditions. Connotations and associations of the adjective ‘grey’ vary due to the ambiguous attitude to it.